2019
DOI: 10.1111/bjep.12336
|View full text |Cite
|
Sign up to set email alerts
|

The role of academic buoyancy and emotions in students’ learning‐related expectations and behaviours in primary school

Abstract: Background. Academic buoyancy refers to students' ability to come through ordinary challenges they face in the academic context, and it can positively contribute to students' beliefs and behaviours in learning situations. Although buoyancy has been found to be related to positive academic outcomes, previous studies have not examined how buoyancy influences academic emotions in learning situations and how these emotions further affect students' learning-related expectations and behaviours. Aims. This study inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 43 publications
2
30
0
Order By: Relevance
“…Academic buoyancy is the capacity to respond effectively to minor academic adversities (Martin & Marsh, 2009). Studies have shown that higher domain general academic buoyancy is related to adaptive educational outcomes in secondary school students (e.g., Malmberg, Hall, & Martin, 2013; Martin et al, 2013) including higher positive, and lower negative, achievement emotions in primary and secondary school students (e.g., Hirvonen et al, 2019; Martin et al, 2010; Putwain et al, 2012). Studies linking domain general academic buoyancy to aggregated achievement in mathematics and reading have shown equivocal results, however, with some reporting statistically significant relations but others not (e.g., Collie et al, 2015; Martin, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Academic buoyancy is the capacity to respond effectively to minor academic adversities (Martin & Marsh, 2009). Studies have shown that higher domain general academic buoyancy is related to adaptive educational outcomes in secondary school students (e.g., Malmberg, Hall, & Martin, 2013; Martin et al, 2013) including higher positive, and lower negative, achievement emotions in primary and secondary school students (e.g., Hirvonen et al, 2019; Martin et al, 2010; Putwain et al, 2012). Studies linking domain general academic buoyancy to aggregated achievement in mathematics and reading have shown equivocal results, however, with some reporting statistically significant relations but others not (e.g., Collie et al, 2015; Martin, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although academic buoyancy shows positive relations with adaptive beliefs, affect, and behaviors in primary and secondary school students (e.g., Hirvonen, Yli-Kivistö, et al, 2019; Hirvonen, Putwain, et al, 2019; Martin, Colmar, Davey, & Marsh, 2010, 2013; Putwain, Connors, Symes, & Douglas-Osborn, 2012), relations between academic buoyancy and achievement are equivocal. Putwain, Daly, Chamberlain, and Saddredini (2016) showed that domain general academic buoyancy positively predicted performance in aggregated scores for English, science, and mathematics secondary school exit examinations (β = .16), after controlling for concurrent relations with test anxiety.…”
Section: Academic Buoyancymentioning
confidence: 99%
“…Using samples of secondary school students, academic buoyancy has been shown to be related to higher adaptive cognitions (e.g., self-efficacy and valuing of school) and behaviours (e.g., effort and planning), and lower maladaptive cognitions (e.g., uncertain control and failure avoidance), emotions (academic and test anxiety), and behaviours (self-handicapping) in cross-sectional designs (Malmberg, Hall, & Martin, 2013;Martin & Marsh, 2006;Putwain et al, 2012). In more sophisticated longitudinal designs, also with secondary school students, academic buoyancy has been shown to predict subsequent lower academic and test anxiety and other unpleasant academic emotions (boredom, hopeless, and shame), school stress, uncertain control, emotional instability, and neuroticism, and higher subsequent pleasant academic emotions (enjoyment, hope and pride), self-efficacy, planning, and persistence (Hirvonen, Yli-Kivistö, Putwain, Ahonen, & Kiuru, 2019;Hirvonen, Putwain, Määttä, Ahonen, & Kiuru, 2019;Martin et al, 2010;Martin, Ginns, Brackett, & Malmberg, 2013;Putwain et al, 2016).…”
Section: Cognitions and Affectmentioning
confidence: 99%
“…Previous research has linked academic buoyancy to various student outcomes such as school satisfaction (Hoferichter et al, 2021 ), high hope and enjoyment (Hirvonen et al, 2020 ), measures of achievement (for a review, see Datu & Yang, 2018 ) and has indeed been shown to buffer the effect of minor adversities on academic achievement (Hoferichter et al, 2021 ). Everyday academic adversity is less likely to cause a drop in performance for students with strong academic buoyancy (Putwain et al, 2020a , b ).…”
Section: Introductionmentioning
confidence: 99%